Shariah Disclosure and the Performance of Islamic Financial Institutions - Musleh Al-Sartawi, Abdalmuttaleb M.A. (Asian Journal of Business and Accounting, 2020)
Manuscript type: Research paper Research aims: This study aims to shed light on the relationship between Shariah disclosure and the performance (social performance and firm value) of listed Islamic financial institutions in the Gulf Cooperation Council (GCC) countries. Design/Methodology/Approach: A checklist based on Islamic standard setters that is based on previous disclosure studies is developed to gauge the level of Shariah disclosures. Data are gathered from the annual reports of the Islamic financial institutions (IFIs) in the GCC for the year ending 2017. Research findings: The findings show a negative and significant relationship between Shariah disclosure and social performance; they also show a positive and insignificant relationship with Tobin’s Q. This outcome could be attributed to the corporate social responsibility (CSR) activities which create financial burdens for the IFIs. With high levels of disclosure, there is a trade-off between the two. Theoretical contribution/Originality: This paper contributes to literature by developing a new disclosure index based on the Shariah perspective in relation to CSR engagement of the IFIs. The findings are noteworthy to the IFIs since CSR practices need to be entrenched into the working practices. They are also expected to generate positive contributions to the social good of the Islamic society, thereby fulfilling justice and equality in lieu of the Islamic concepts. Practitioner/Policy implication: From a more practical perspective, this study is useful to regulators and policy makers who wish to incorporate CSR into their Shariah-compliant policies. Based on the findings, it is vital that CSR standards be implemented as a mandatory policy for the IFIs. Doing so would enhance their social performance, thus enhancing a higher level of Shariah disclosures. Research limitation/Implications: The findings are limited to the context of Shariah disclosure and the GCC listed firms. The sources of data used for this study are also confined to the annual reports and the websites of the IFIs. In this regard, the outcome may not be applicable to all markets. Keywords: GCC Countries, Islamic Financial Institutions, Shariah Disclosure, Shariah Governance, Shariah Supervisory Board, Social Performance JEL Classification: G280, G380, M140, Z120